Celebrating the marvellous surrealism in architecture - Spiller, Neil (Architectural design, 2018)
We are entering a new era of architecture that is technologically enhanced, virtual and synthetic.. Founded by poet Andre Breton in Paris in 1924 as an artistic, intellectual and literary movement, architects such as Le Corbusier, Diller + Scofidio, Bernard Tschumi and John Hejduk realized its evocative powers to propel them to 'starchitect' status. Surrealism, with its multiple readings of the city, its collage semiotics, its extruded forms and artificial landscapes, is an ideal source for contemporary architectural inspiration.